ANALISIS KEKUATAN GESER BALOK BETON MUTU TINGGI - Oesman, Mardiana
An experimental investigation was conducted to study the behavior and the mechanism of shear strength of reinforced concrete beams without shear (web) reinforcement. A total of 9 shear critical reinforced concrete beams without shear (web) reinforcement were tested on a loading frame, and a complete loading load-midspan deflection curves were obtained. The experimental variables were the concrete compressive strength and shear span-to-depth ratio. Concrete strength (fc') was varied between 30 MPa and 70 MPa. The shear span-to-depth ratio a/d was varied between 2.5 and 5.0. And the longitudinal reinforcement ratio p was 1.46%. The test results were analyzed and compared with the strength predicted by Indonesian code SK SNI T-15-1991-03. The tests results indicated that Indonesian code SIC SNI T-15-1991-03 does not accurately predict the effect of a/d, and is conservative for high strength reinforced concrete beams without shear (web) reinforcement with aid greater than 3 in which the safety factor reaches 6.5. For a/d less than 3, the behavior of shear strength of high strength reinforced concrete beams without shear (web) reinforcement is similar to the behavior of shear strength of normal reinforced concrete beams without shear (web).